Elaboración de procedimientos operativos estandarizados de saneamiento en la inocuidad de la mortadela especial en el taller de procesos cárnicos - Basurto Santos, Luis Vicente (2017)
The goal of this research was to implement standardized procedures in the ESPAM MFL process about Meat Shop to control the safe of the special sausages produced in its production line through the general BPM (Good Manufacturing Practices) and POES (Standardized Operating Procedures for Sanitation), for which a diagnostic was made before the implementation and after that one to evaluate whether the implementation had an impact or not. The diagnostic was made through a check list elaborated under the conditions of the BPM registration 3253, obtaining an initial average of compliance of 57%, to verify if the product complies with the microbiological requirements, 5 samples were collected for different periods of process and 5 samples it was during and after the implementation, being carried out the analyzes established in the norm INEN 1340. The obtained results demonstrated that the areas of storage, personnel and the operations of production were the influents in the microbiological part, being that the sample 4 exceeded the limits of enter bacteria (1.3x102 CFU / g) produced by contamination of shrimp odors found in production areas. After the implementation of POES and BPM in the line sausages processes, a mean percentage of compliance was found of 81.8% and that the microbiologically evaluated samples were in the established ranges, concluding that the implementation of the general procedures BPM and POES contribute to ensure safety it ensured during the preparation of the special sausages.